2011
DOI: 10.1104/pp.110.170936
|View full text |Cite
|
Sign up to set email alerts
|

Pithy Protection: Nicotiana attenuata’s Jasmonic Acid-Mediated Defenses Are Required to Resist Stem-Boring Weevil Larvae    

Abstract: Folivory is the best studied plant-herbivore interaction, but it is unclear whether the signaling and resistance traits important for the defense of leaves are also important for other plant parts. Larvae of the tobacco stem weevil, Trichobaris mucorea, burrow into stems of Nicotiana attenuata and feed on the pith. Transgenic N. attenuata lines silenced in signaling and foliar defense traits were evaluated in a 2-year field study for resistance against attack by naturally occurring T. mucorea larva. Plants sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 89 publications
(94 reference statements)
0
33
0
Order By: Relevance
“…The stems of N. attenuata are often attacked by herbivores, including stem borers (Diezel et al, 2011b;Lee et al, 2016), and are very important for plant fitness (Machado et al, 2016). We observed a strong up-regulation of defensive secondary metabolites in the stems in response to M. sexta attack (Fig.…”
Section: Iaa Specifically Potentiates the Herbivore-induced Accumulatmentioning
confidence: 65%
See 2 more Smart Citations
“…The stems of N. attenuata are often attacked by herbivores, including stem borers (Diezel et al, 2011b;Lee et al, 2016), and are very important for plant fitness (Machado et al, 2016). We observed a strong up-regulation of defensive secondary metabolites in the stems in response to M. sexta attack (Fig.…”
Section: Iaa Specifically Potentiates the Herbivore-induced Accumulatmentioning
confidence: 65%
“…The stem of N. attenuata is vital for its reproduction and can be attacked by a wide variety of organisms, including vertebrates and invertebrate stem borers (Machado et al, 2016;Diezel et al, 2011b). We observed that real and simulated M. sexta attack induced anthocyanin accumulation in the stems, an effect that could not be reproduced by MeJA or IAA treatments alone, but by the combination of these two hormones.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In fact, according to the geometric morphometric analysis, genetic analysis, and Barber's descriptions (1935), this group seems to belong to Trichobaris mucorea, a species reported parasitizing Datura wrightii and other solanaceous plants such as Nicotiana attenuata (Barber 1935;Diezel et al 2001). b Transformation grid of CV1 describe the shape of T. soror's aedeagi, whereas c CV2 describes the shape of weevils found in RC population Finally, this work is the first phylogeographic study of a species of the Trichobaris genus, which includes many species that are pests of potato, tomato, and tobacco crops.…”
Section: Discussionmentioning
confidence: 98%
“…We transformed N. attenuata plants using RNAi technology with an inverted-repeat (ir) sequence of their endogenous CAD gene to silence two stem-expressed NaCADs, referred to as ir-CAD plants. The ecological importance of lignification in N. attenuata-Trichobaris mucorea (tobacco stem weevil) interaction in the field has been reported recently using these NaCADsilenced plants (Diezel et al, 2011). Here, we addressed the following questions by conducting a series of experiments with N. attenuata ir-CAD plants grown in both the GH and the plant's native habitat in Utah.…”
mentioning
confidence: 99%